Collection of holding tax in local government of Bangladesh: A case study of Meherpur sadar upazilla - Islam, Md Nabirul (BRAC University, 2010)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Governance and Development, 2009.